ELECTRON MICROSCOPIC STUDIES ON THE INDIRECT FLIGHT MUSCLES OFDROSOPHILAMELANOGASTER : II. Differentiation of Myofibrils - Shafiq, S. Ahmad (The Rockefeller University Press, 1963)
The differentiation of the indirect flight muscles was studied in the various pupal stages of Drosophila. Fibrillar material originates in the young basophilic myoblasts in the form of short myofilamants distributed irregularly near the cell membranes. The filaments later become grouped into bundles (fibrils). Certain "Z bodies" appear to be important during this process. The "Z bodies" may possibly be centriolar derivatives and are the precursors of the Z bands. The first formed fibrils (having about 30 thick myofilaments) are already divided into sarcomeres by Z bands. These sarcomeres, however, seem to be shorter than those of the adult fibrils.The H band differentiates in fibrils having about 40 thick myofilaments; the fibrils constrict in the middle of each sarcomere during this process. The individual myofibrils increase from about 0.3 µ to 1.5 µ in diameter during development, apparently by addition of new filaments on the periphery of the fibrils. The ribosomes seem to be the only cytoplasmic inclusions which are closely associated with these growing myofibrils. Disintegration of the plasma membranes limiting individual myoblasts was commonly seen during development of flight muscles, supporting the view that the multinuclear condition of the fibers of these muscles is due to fusion of myoblasts.